AN EMPIRICAL STUDY ON THE OPPORTUNITY AND CONSTRAINTSFOR SPICE EXPORTER - SANTOSH KUMAR RAM (International Journal of Multidisciplinary Research and Studies, 2020)
Export is widely regarded as the primary driver of economic expansion as it has taken on an increasingly significant role in the development of every nation. In order to achieve quick growth and pay for the country's vital imports, India needs a substantial amount of foreign currency. It is necessary to generate millions of job openings in order to put today's young people to productive use in the construction of the nation. Earning it through exports is the most reliable way to receive foreign currency over the long term, despite the fact that the country has other potential sources of this currency. Not only does the export of highly valued traditional products bring in foreign currency, but it also provides employment for a significant number of people. When compared to other conventional items, the prices of spices on both the local and international markets are significantly higher. This is the manufacture of spices in India requires a significant amount of semi-skilled and unskilled labour. The transformation of the international trade landscape brought about by the formation of the WTO has had a major impact on India's spice exports.